Development of a new scale for the measurement of interprofessional collaboration among occupational therapists, physical therapists and speech-language therapists - Kohei Ikeda; Satoshi Sasada (SAGE Publishing, 2022)
Background/Objective The purpose of this study is to develop and validate an instrument to assess interprofessional collaboration by occupational therapists, physical therapists, and speech-language therapists. Methods Item development consisted of a review of interprofessional collaboration and group interviews with occupational therapists, physical therapists, and speech-language therapists. The developed items were surveyed on a 4-point Likert scale among occupational therapists, physical therapists, and speech-language therapists. Ceiling effects, floor effects, and item-total correlation analysis for each item, as well as constructs, internal consistency, and cross-cultural validity of the scales were evaluated. Results A total of 47 items were extracted for evaluation and 28 items with five factors ("team-oriented behavior," "exchange of opinions," "flexible response," "sharing the whole picture of the patient," and "coordination of support methods") were retained after the evaluation. The correlation coefficients of the five factors ranged from 0.48 to 0.72. The total score of each factor and the total score of all 28 items were compared for occupational therapists, physical therapists, and speech-language therapists, and the result showed that was no statistically significant difference between the total scores of all factors and the job titles. The Cronbach's alpha coefficients for the five factors are 0.842, 0.840, 0.805, 0.732, and 0.734 for the first, second, third, fourth, and fifth factors, respectively. Conclusions The developed scale includes items aimed at facilitating patients' activities of daily living through interprofessional collaboration, and its content reflects the expertise of occupational therapists, physical therapists, and speech-language therapists.